2001
DOI: 10.1104/pp.126.4.1688
|View full text |Cite
|
Sign up to set email alerts
|

Electrodiffusional Uptake of Organic Cations by Pea Seed Coats. Further Evidence for Poorly Selective Pores in the Plasma Membrane of Seed Coat Parenchyma Cells

Abstract: In developing seeds, the permeability of the plasma membrane of seed coat parenchyma cells is crucial for the supply of nutrients to the embryo. Here, we report characteristics of the transport of the organic cation choline and the basic amino acid l-histidine (His; cation at pH 5, electroneutral at pH 7) into isolated seed coats of pea (Pisum sativum). Supplied at sub-micromolar concentrations, choline ϩ accumulated in the seed coat tissue 5.1 Ϯ 0.8-fold, His ϩ 2.4 Ϯ 0.3-fold, and His 0 1.3 Ϯ 0.2-fold. Taking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…This confirms the supply follows demand model of assimilate unloading proposed by van Dongen et al (2001). According to this model, which is originally based on experiments with seed coats of legume seeds, the supply of nutrients by the maternal seed coat is determined by the demand of the developing embryo.…”
Section: Implications For the Regulation Of Phloem Transport To The Sinksupporting
confidence: 57%
See 1 more Smart Citation
“…This confirms the supply follows demand model of assimilate unloading proposed by van Dongen et al (2001). According to this model, which is originally based on experiments with seed coats of legume seeds, the supply of nutrients by the maternal seed coat is determined by the demand of the developing embryo.…”
Section: Implications For the Regulation Of Phloem Transport To The Sinksupporting
confidence: 57%
“…The concentration gradient acts as the driving force for unloading of fresh nutrients into the apoplast. For pea, evidence exists that poorly selective pores are present in the plasma membrane of seed coat parenchyma cells to facilitate the unloading of assimilates (de Jong et al, 1996(de Jong et al, , 1997van Dongen et al, 2001). Also in wheat, nucellus unloading appears to be a passive process, thus driven by the concentration gradient (Wang and Fisher, 1995).…”
Section: Implications For the Regulation Of Phloem Transport To The Sinkmentioning
confidence: 99%
“…In legume seeds, results from inhibitor studies led to the proposal that nonselective passive pores are responsible for sucrose efflux (van Dongen et al, 2001;Ritchie et al, 2003). Neither the predicted antiporters nor the nonselective pores have been identified at the molecular level to date.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular basis for the efflux of these solutes is still unknown. It has been suggested that in seed coats of common bean (Phaseolus vulgaris) and broad bean (Vicia faba) sucrose is released by an H + -antiport mechanism , whereas work in our group on pea has provided evidence for poorly selective pores in the plasma membrane of seed coat parenchyma cells that allow the passage of sugars, amino acids and possibly inorganic ions as well (de Jong et al, 1996(de Jong et al, , 1997van Dongen et al, 2001).…”
Section: Introductionmentioning
confidence: 94%